National Early Warning Score Is Modestly Predictive of Care Escalation after Emergency Department-to-Floor Admission - Sutherland, Mark E.; Yarmis, Samantha J.; Lemkin, Daniel L.; Winters, Michael E.; Dezman, Zachary D.W. (The Journal of emergency medicine, 2020)
Decompensation on the medical floor is associated with increased in-hospital mortality. Our aim was to determine the accuracy of the National Early Warning Score (NEWS) in predicting early, unplanned escalation of care in patients admitted to the hospital from the emergency department (ED) compared to the Shock Index (SI) and the quick Sepsis-Related Organ Failure Assessment (qSOFA) score. We conducted a retrospective cohort study of patients admitted directly from the ED to monitored or unmonitored beds (November 9, 2015 to April 30, 2018) in 3 hospitals. Interhospital transfers were excluded. Patient data, vital status, and bed assignment were extracted from the electronic medical record. Scores were calculated using the last set of vital signs prior to leaving the ED. Primary endpoint was in-hospital death or placement in an intermediate or intensive care unit within 24 h of admission from the ED. Scores were compared using the area under the receiver operating curve (AUROC). Of 46,018 ED admissions during the study window, 39,491 (85.8%) had complete data, of which 3.7% underwent escalation in level of care within 24 h of admission. NEWS outperformed (AUROC 0.69; 95% confidence interval [CI] 0.68–0.69) qSOFA (AUROC 0.63; 95% CI 0.62–0.63; p < 0.001) and SI (AUROC 0.60; 95% CI 0.60–0.61; p < 0.001) at predicting unplanned escalations or death at 24 h. This multicenter study found NEWS was superior to the qSOFA score and SI in predicting early, unplanned escalation of care for ED patients admitted to a general medical-surgical floor.